Highly stable Ni/SiC catalyst modified by Al2O3 for CO methanation reaction. Issue 12 (25th January 2016) - Jin, Guojing; Gu, Fangna; Liu, Qing; Wang, Xiaoyan; Jia, Lihua; Xu, Guangwen; Zhong, Ziyi; Su, Fabing
Abstract : Ni/Al2 O3 –SiC exhibits good catalytic activity and stability due to excellent heat conductivity of SiC and enhanced interactions between Ni and support by alumina modification, thus inhibiting the migration of Ni particles. Abstract : It is still a great challenge to prevent sintering of supported Ni catalysts in highly exothermic reactions. To address this problem, in this work, highly thermal conductive and stable SiC is explored as a Ni catalyst support for CO methanation to produce synthetic natural gas; simultaneously, Al2 O3 is utilized to modify the SiC surface to enhance the interaction between the metal and support and restrain the Ni active component from sintering or loss during the reaction. A series of Ni/Al2 O3 –SiC catalysts were successfully prepared by the co-deposition–precipitation method. The catalysts were investigated by N2 adsorption, XRD, SEM/EDS, TEM, XPS, H2 -TPR, H2 -TPD and TG. The elemental mapping images indicated that the introduced Al2 O3 particles were uniformly deposited on the surface of the SiC support, which evidently enhanced the interaction between Ni and the support by forming Ni–Al2 O3 complexes as proved by H2 -TPR results. The Ni/Al2 O3 –SiC catalyst with an optimal amount of Al2 O3 content showed a high catalytic activity and strong resistance to sintering, which can be attributed to two main factors: (1) the addition of Al2 O3 can enhance the interactions between Ni and the support, thus inhibiting the migration of Ni particles on the support surface and improving the dispersion of them; (2) the superior heat conductivity of SiC can decrease the generation of hot spots in the catalyst bed.